Graphic Organizer-Based Science Literacy Learning Models In Elementary Schools - Fitria, Y.; Alwi, N. A.; Eliasni, R.; Chandra, C.; Kharisma, A. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
The purpose of this study is to test the level of effectiveness of graphic organizer-based scientific literacy learning models in elementary schools. This study’s goal is to evaluate the efficacy of elementary school scientific literacy learning approaches that rely on visual organizers. Plomp design development was used to perform the study. The three primary phases of this kind of Plomp development research methodology were preliminary research, prototype, and assessment. Students at Indonesia’s West Sumatra province’s elementary schools in the fourth grade served as the study’s subjects. The study’s findings have a significance level of 0.05, or 0.000 0.05. In the experimental classes 1 and 2, it can be concluded that there is a substantial difference between student learning results before and after using the graphic organizer-based scientific literacy learning approach. The N-gain value for the experimental class 2 is 0.712 in the high category and the N-gain value for the experimental class 1 is 0.628 in the medium category. In conclusion, the graphic organizer-based scientific literacy learning model is effectively used in class IV of elementary schools.